Game theory and economic modelling - Kreps, David M.; Oxford eBooks (Oxford : Clarendon Press, 1990)
The advent of noncooperative game theory over the past two decades has brought about a mild revolution in economics. This book presents an accessible, non-technical discussion of the basic concepts from noncooperative theory, and explores the strengths, weaknesses, and future of the theory as a tool for economists.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Game theory; Econometric models; Cooperation; Competition; Electronic books